High and low performing schools in South Africa: Metaphors as a lens to understand teachers' views of school organisation. (2022) - Ehren, M.; Paterson, A.; Camphuijsen, M.; Baxter, J.
Highlights: Teachers in both low and high performing schools use the same four metaphors to describe their school organisation: family, factory, hospital and warzone. These vary however according to their lived experiences, including those outside of the school (e.g. family relations). Metaphors also vary within the school according to teacher's wider roles and responsibilities and students they teach, while different metaphors are used for different aspects of the school organisation. Given their influence on school staff behaviours, their decision-making and communication, metaphors provide an important lens through which to understand the wide disparity in school quality and performance in South Africa.